Analyzing the Role of Emotional Intelligence on Job Satisfaction Among Academicians Working in Management Institutions in NCR, India - Dr. Vijit Chaturvedi, Gurpreet Kaur, GP Capt Vinod Kumar (International Journal of Advanced Science and Technology, 2020)
The emotional intelligence has its practical implications in different aspects of work and study, with reference to teaching professionals it holds important position as it is the EI of the teaching professional which not only affects the self-control or awareness of the teaching professionals but also directs, regulates and affects the future of the students. Job satisfaction represents a complete array of factors which affect the contentment and delivery from an employee.